Variation in situation-specific engagement among lower secondary school students. (February 2018) - Pöysä, Sanni; Vasalampi, Kati; Muotka, Joona; Lerkkanen, Marja-Kristiina; Poikkeus, Anna-Maija; Nurmi, Jari-Erik
Abstract: The majority of previous research has examined school engagement as an overall student characteristic. The present study contributes to the field by examining variation in students' situation-specific engagement from one lesson to another and by investigating situational determinants of such variation. An intensive one-week lesson-to-lesson data collection was conducted in four lower secondary school classrooms. Students rated their situation-specific engagement at the end of each lesson with a mobile-based InSitu instrument. Data comprising a total of 57 students and 1328 ratings were analyzed with two-level hierarchical multivariate model (between students, and within students between lessons). The results indicated substantial within student variation in engagement between lessons which was predicted by school subjects. Students reported highest situational engagement and lowest disaffection in lessons of non-academic subjects. The findings extend prior literature by specifying factors affecting students' situation-specific engagement and by unraveling effects due to variation within and between students. Highlights: Students' engagement varied from lesson to another. Situation-specific engagement varied depending on the subject being studied. Situation-specific engagement varied depending on students' academic achievement.